"Green Marketing and Sustainable Packaging Innovations: Driving Consumer Engagement and Environmental Impact" (Journal of Informatics Education and Research, 2026)
Amidst the growing focus on sustainability, the marketing field has also been affected. The domain of marketing has also come up with novel concepts like green marketing. The idea of sustainable and ecological marketing focuses on practices of developing and promoting products which are environmentally friendly. Packaging being one of the important tenets of marketing, through this paper I have carried out the qualitative research to explore the intersection of green marketing and Sustainable Packaging Innovations focusing on how these practices drive consumer engagement and contribute to environment sustainability.